1982
DOI: 10.1152/ajpgi.1982.242.1.g65
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal filtration-secretion due to increased intraluminal pressure in rabbits

Abstract: The mechanism of changes in small intestinal transport due to acutely increased intraluminal hydrostatic pressure (IHP) was investigated in detail using perfused in vivo rabbit intestinal segments. IHP affected passive transport in vivo by increasing effective mucosal surface area in the small intestine (indicated by 3HOH transport and tissue architectural changes) and increasing small intestinal permeability (indicated by a proportionately greater increase in mannitol than erythritol secretory clearance). IHP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Intestinal distention created by elevating the intestinal luminal perfusate outflow cannula has been used to create high intraluminal pressures. 47,48 We confirmed that this method resulted in the desired pressure by directly measuring intraluminal pressure in the outflow cannula via a 3-way stopcock connected to a pressure transducer. Similar to results of previous studies, 8,[49][50][51] we also detected a single increase in intraluminal pressure after distention.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Intestinal distention created by elevating the intestinal luminal perfusate outflow cannula has been used to create high intraluminal pressures. 47,48 We confirmed that this method resulted in the desired pressure by directly measuring intraluminal pressure in the outflow cannula via a 3-way stopcock connected to a pressure transducer. Similar to results of previous studies, 8,[49][50][51] we also detected a single increase in intraluminal pressure after distention.…”
Section: Discussionmentioning
confidence: 54%
“…32 Increases in permeability have been reported following intraluminal distention of the intestine of various species, including horses. 7,15,47 Distention to an intraluminal pressure of 30 cm H 2 O causes multifocal areas of necrosis in the mucosa of rabbits. 47 However, results of a study evaluating equine jejunum revealed that although blood flow is reduced during distention, the effect is more accentuated in the serosa than the mucosa and submucosa.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in net chloride reabsorption, however, is also predicted from the mode of operation of the Cl -/HCO 3 exchanger. Experimental work has shown that when intraluminal pressure is increased, the driving forces for filtration secretion are augmented [8,9,10]. Further, active solute transport mechanisms may be impaired in patients with ileus, as it has been shown experimentally when intraluminal pressures are increased [7,8].…”
Section: Discussionmentioning
confidence: 94%
“…The effect of TNF‐ α , on disrupting tight junctions in the intestinal epithelium [15] and on increasing tight junction permeability in intestinal epithelial cells, is mediated through activation of NF‐ κ B [16]. An increase in intestinal permeability, caused by a rise in the intestinal intraluminal pressure, has also been reported in animal models of in vivo rabbit intestinal segments [17]. TRAPS is characterized by periodically occurring inflammation, believed to be due, in part, to inappropriately functioning TNFRSF1A and subsequent prolonged action of TNF‐ α .…”
Section: Discussionmentioning
confidence: 99%